COMPLIANCE LEVEL ANALYSIS OF COVID-19 HEALTH PROTOCOL AMONG KARANG TARUNA MEMBERS AT PANDANLANDUNG VILLAGE, MALANG - Hartati Eko Wardani; Tika Dwi Tama; Rara Warih Gayatri; Putri Djamilah Wahidah (Universitas Airlangga, 2023)
Introduction: One of the keys to success in efforts to overcome the COVID-19 pandemic is to comply with health protocols. The COVID-19 health protocol compliance level is known to be low in the adolescent age group. The low level of compliance is related to the role of Karang Taruna as a village-level organization in providing education and examples to their peers, namely adolescents. Aims: This study was conducted to describe the level of compliance of Karang Taruna members in Pandanlandung Village, Wagir District, Malang Regency to the COVID-19 Health Protocol. Methods: The design used in this research is cross sectional with a quantitative descriptive method. This research was conducted in March-October 2021 with the number of respondents as many as 24 members of the Karang Taruna Pandanlandung Village who were selected using a total sampling technique. Results: This research study found that the compliance level of members of the Karang Taruna Pandanlandung Village was in the